PENGUASAAN HASIL PEMBELAJARAN ILMU PENGETAHUAN ALAM MELALUI MODEL PAIKEM DENGAN MEDIA SLIDE PADA SISWA KELAS V MADRASAH IBTIDAIYAH NEGERI 2 SAMBAS - Topik Topik (Cross-border, 2019)
This research uses a qualitative approach and descriptive type of research. Data collection techniques using observation, interviews and documentation. While the data sources in this study were science teacher class V as the main data, the principal as supporting data and documents such as lesson plans, student scores, and research photos as secondary data. As for data analysis techniques, researchers used data reduction, data display and drawing conclusions. The data validity checking technique used was the triangulation technique and the member check technique. The results showed that: The teacher planned science learning through the PAIKEM model with slide media for the fifth grade students with the following planning steps: 1) the teacher prepared the learning material; 2) the teacher formulates the learning objectives contained in the lesson plan; 3) the teacher prepares the steps for teaching and learning activities; 4) formulating learning models and media; 5) formulate a learning evaluation. Class V teachers carry out science learning through the PAIKEM model with slide media with several stages: 1) the teacher opens the lesson and does a pre-test; 2) the teacher delivers learning materials through the PAIKEM model with slide media; 3) the teacher closes the lesson. Class V teachers evaluate science learning through the PAIKEM model with slide media for fifth grade students, namely; 1) conducting a pre-test; 2) conduct an evaluation at the end (post test). Based on the results of the evaluation of mastery of science learning outcomes through the PAIKEM model with slide media in grade V, students have been able to master the science learning material about mentioning movement tools in animals and humans and their functions correctly, precisely and confidently. Students are able to master the learning outcomes of Natural Sciences (IPA) on these materials in 1 (one) meeting for 2 x 45 minutes.